The Effect of Price, Product Quality, Promotion, Brand Image, and Location on the Purchasing Decision of Traffic Bun Grancity Balikpapan - Fitriana Fitriana; Syahril Hasan; Hikma Hasbi (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to determine the influence of price, product quality, promotion, brand image, and location on the purchasing decision of Traffic Bun Balikpapan. The research location is at the Traffic Bun Balikpapan store in Grand City Balikpapan, Jl. Sinarmas Land, Grand City, Ruko Golden Boulevard Blok AC, No.41, Batu Ampar District, north Balikpapan District. The data used are primary data obtained directly from the division of questionnaires. The sample in this study was 60 respondents. Based on the multiple linear regression analysis results, the value of the correlation coefficient (R) was obtained at 0.627 and the coefficient of determination (R²) at 39.3%. The simultaneous test results (Test F) showed that the calculated F was 6.999 > F table of 2.39, meaning that price, product quality, promotion, brand image, and location simultaneously had a significant effect on the decision to buy Traffic Bun Balikpapan. The results of the partial test (Test t) showed that the price variable (X1) t count of -2.734 > t of the table of 2.00488, which means that the price variable partially had a negative and significant effect on purchasing decisions. The product quality variable (X2) t count of 2.731 > t table of 2.00488, which means that the quality variable of the product partially had a positive effect and was significant to the purchase decision. The promotion variable (X3) t count is -2,061 > t table is 2.00488, which means the promotion variable partially negatively and significantly affects the purchase decision. The brand image variable (X4) t count is 2,809 > t table is 2.00488, which means the brand image variable partially has a positive and significant effect on purchasing decisions. The location variable (X5) t counts by 2,618 > t table of 2.00488, which means that the location variable partially has a positive and significant effect on purchasing decisions.